2016
DOI: 10.1007/s10948-016-3939-7
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Magnetic Properties of Bi1.7Pb0.3Sr2Ca2Cu3O10+δ Added with Nano Y

Abstract: Bi 17 Pb 0.3 Sr 2 Ca 2 Cu 3 O 10+δ superconductor samples were synthesized by the conventional solid-state reaction method. To study the effects of the addition of yttrium nanoparticles to the superconducting system, nano Y 2 O 3 was introduced by small weight percentages (0.2, 0.4, 0.6, 0.8, and 1.0 wt%) in the first step of the synthesis process. Phase identification and microstructural characterization of the samples were investigated using X-ray diffraction and scanning electronic microscopy (SEM). Energyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Accordingly, the orthorhombic structure continues to exist in all samples. In Table 1, it is seen that there is no change the volume fraction of the 2223-phase in nano-Y2O3 addition samples compared to the undoped sample [14]. The nano-Y2O3 addition has been effectively added to the phase stability of the BSCCO systems.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Accordingly, the orthorhombic structure continues to exist in all samples. In Table 1, it is seen that there is no change the volume fraction of the 2223-phase in nano-Y2O3 addition samples compared to the undoped sample [14]. The nano-Y2O3 addition has been effectively added to the phase stability of the BSCCO systems.…”
Section: Resultsmentioning
confidence: 95%
“…It was found that critical temperature and critical current density increased up to x=0.7 wt%. Again, in a study conducted by Oboudi in 2016 [14], nano Y2O3 was added to Bi1,8Pb0,4Sr2Ca2Cu3O10+y superconductor samples with different weight percentages. As the additive ratio increased, the current density increased by 200% and superconductivity transition temperature increased by 3%.…”
Section: Introductionmentioning
confidence: 99%
“…J c clearly followed the same pattern as T c with x. J c rises from roughly 614 A/cm 2 for the pure sample to 691 A/cm 2 and 1034 A/cm 2 for x = 0.025 of Sm and la, respectively, as shown in Figures 6 and 7. This improvement might be attributed to Sm and La replacements functioning as pinning centers to stabilize vortices and improve inter-grain and intergranular flux pinning [39,40]. However, La has a bigger influence on the flux pinning and critical current density of the prepared samples than Sm.…”
Section: Critical Current Density (J C ) Measurementsmentioning
confidence: 97%
“…Generally, the major of the studies done so as to augment the superconducting characteristics of BSCCO is the addition or substitution process of the elements to the matrix. Recently, nanoparticle addition or substitution processes to Bi-2223 phase is condensed day by day with the help of the developing technology [20][21][22][23][24][25][26][27][28][29][30]. Additionally, introduction of nanoparticles in the high temperature superconducting systems has attracted significant attention due to the fact that these particles are thought as simply controlled and productive instrument to develop superconducting characteristics.…”
Section: Introductionmentioning
confidence: 99%